Metoda dvourozměrné diferenční gelové elektroforézy (2-D DIGE) a její využití v proteomice - Vítámvás, Pavel; Kosová, Klára; Škodáček, Zbyněk; Prášil, Ilja Tom (Chemické listy, 2010)
Two-dimensional differential gel electrophoresis (2-D DIGE) is a modification of the well-known twodimensional method (2-DE). The new method enables separation of two protein samples on one 2-D gel thus avoiding problems associated with reproducibility of 2-D gels and makes it possible to compare different samples. The only extra step in 2-D DIGE is sample labelling with cyanine fluorescent dyes (CyDyesTM). Two types of labelling are used: with succinimidyl esters and with maleimide derivatives of the dyes to label lysine and cysteine residues, respectively. For detection and quantification of protein spots in gels, a special fluorescent scanner or a CCD camera are required. From densitometric analysis of 2-D DIGE gels, sets of multidimensional data are obtained, which are then analysed by statistical methods. Protein spots can be cut from 2-D DIGE gels and further analysed by MS. The 2-D DIGE method affords much better quantification of proteins in samples. The separation of two samples at a time leads to a large reduction in the used amount of 2-D gels.
Keywords: 2D gelová elektroforéza; proteomika; Financing, Organized; Electrophoresis, Gel, Two-Dimensional; Proteomics; financování organizované